Pharmacovigilance practice on off-label high-dose of vancomycin in severely ill children - Qin, Min; Chen, Wenwen; Lu, Bin; Deng, Yi (Frontiers in Pharmacology, 2025)
PurposeTo investigate the safety of off-label high-dose vancomycin use in severely ill children and explore strategies to control risks.MethodsA case of acute kidney injury caused by off-label high-dose vancomycin (exceeding 40 mg/kg/day) in the Pediatric Intensive Care Unit (PICU) was analyzed. A retrospective case-control review of vancomycin treatment in 39 PICU patients from January to June 2020 were conducted.FindingsAmong the 39 patients, 20 (51.3%) received off-label high-dose vancomycin dosing, and only 53.8% (21/39) underwent blood concentration testing. Five patients (25%; 5/20) in the off-label use group experienced vancomycin-associated adverse reactions, including three cases of severe ones. Based on risk factor analysis, we implemented improvement measures such as increasing the monitoring of vancomycin trough serum concentration, providing individualized drug regimens, enhancing training, and formally documenting off-label drug use. After implementing these measures from July 2020 to December 2022, a total of 86 children in the PICU were treated with vancomycin, and no cases of vancomycin-associated acute kidney injury was observed. The monitoring rate of vancomycin blood concentration increased to 88.4% (76/86).ImplicationsThere is a risk of renal function damage when using high dosage of vancomycin in severely ill children, and healthcare providers should pay special attention to this in clinical medication safety practices.